Effect of Education and Telephone Counseling on Caregiver Strain and Unmet Needs in Family Caregivers and Self-care Behaviors in Patients with Cancer: A Randomized Clinical Trial - Fatemeh Ghorbani; Masoud Zare; Fatemeh Heshmati Nabavi; Hamidreza Behnam Vashani; Alireza Bari (Mashhad University of Medical Sciences, 2020)
Background: Cancer treatment has been increasingly fulfilled on an outpatient basis by family caregivers. The variety and severity of caregivers' responsibilities expose them to physical and mental risks. Investigating the effect of education and telephone counseling on patient and family outcomes requires performing further studies. Aim: This study aimed to determine the effect of education and telephone counseling on caregiver strain and unmet needs in family caregivers and self-care behaviors in cancer patients.   Method: The present randomized controlled trial was conducted on 60 caregivers-cancer patients referred to urban health education clinics in northeastern Iran within 2018-2019. A 20-minute face-to-face training session was held for the caregivers of cancer patients, and seven training pamphlets were given to the caregivers. Moreover, the intervention group received four telephone counseling sessions during three courses of chemotherapy. The strain and unmet needs of caregivers were measured by the Zarit Burden Interview and Supportive Care Needs Survey-Partners and Caregivers questionnaires, respectively. The patient self-care was assessed by the Nail Self-care Diary questionnaire. The data were analyzed by SPSS software (version 16) using an independent t-test and paired t-test. Results: The mean values of caregivers' age were 38.9±12.7 and 37.7±8.6 years in the intervention and control groups, respectively. The results of the independent t-test showed no statistically significant difference between the two groups (P=0.42). The results also revealed that the mean scores of caregiver strain and unmet needs decreased following the intervention, and the mean scores of self-care behaviors increased in the intervention group after the intervention (P=0.001). Implications for Practice: Education and telephone counseling can simultaneously help to follow up problems, improve self-care behaviors in cancer patients, alleviate the caregiver strain, and meet the needs of family caregivers.